2018
DOI: 10.1038/s41598-018-26872-w
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Studies of Nanoporous Si Films with Pitches on the Order of 100 nm —Comparison between Different Pore-Drilling Techniques

Abstract: In recent years, nanoporous Si films have been widely studied for thermoelectric applications due to the low cost and earth abundance of Si. Despite many encouraging results, inconsistency still exists among experimental and theoretical studies of reduced lattice thermal conductivity for varied nanoporous patterns. In addition, divergence can also be found among reported data, due to the difference in sample preparation and measurement setups. In this work, systematic measurements are carried out on nanoporous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Within periodic nanoporous films, the shape variation of individual nanofabricated pores across the whole film can add large uncertainties to the data analysis, along with varied pore-edge defects or roughness to affect the effective pore diameter and thus the neck width. 43,[46][47][48] This makes such periodic nanoporous Si films unsuitable for the study of the phonon MFP distribution.…”
Section: Comparison Between Periodic Nanoslot and Nanopore Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within periodic nanoporous films, the shape variation of individual nanofabricated pores across the whole film can add large uncertainties to the data analysis, along with varied pore-edge defects or roughness to affect the effective pore diameter and thus the neck width. 43,[46][47][48] This makes such periodic nanoporous Si films unsuitable for the study of the phonon MFP distribution.…”
Section: Comparison Between Periodic Nanoslot and Nanopore Patternsmentioning
confidence: 99%
“…The effective 𝑤 value for each neck can be slightly expanded due to the amorphous pore edges, as suggested for nanoporous Si films in electron microscopy studies. 34,46,47…”
Section: Comparison Between Periodic Nanoslot and Nanopore Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches have been suggested to reduce R c , m and improve the membrane temperature uniformity, such as adding high k materials to the membranes [ 120 ]. Furthermore, recent studies showed that the use of an integrated device fabricated from the same device layer as the membrane minimizes the thermal contact resistance between sample and membrane [ 36 , 121 ].…”
Section: Experimental Techniques For Thermal Characterizationmentioning
confidence: 99%
“…Using this approach Lu et al measured the thermal properties of platinum wires and multiwalled carbon nanotubes. Later several researchers used the same approach to measure the thermal properties of Si nanowires, multi- and single-walled carbon nanotubes [ 137 , 138 ], and nanoporous Si films [ 121 ] among others.…”
Section: Experimental Techniques For Thermal Characterizationmentioning
confidence: 99%